A Consistent PCR-RFLP Assay Based on ITS-2 Ribosomal DNA for Differentiation of Fasciola Species - Reza Shafiei; Bahador Sarkari; Abdolali Moshfe (Iranian Journal of Basic Medical Sciences, 2013)
Objective(s): Fascioliasis is a zoonotic parasitic disease caused by liver fluke species of Fasciola hepatica and Fasciola gigantica. Differentiation of these two species, based on their morphological characteristics, is difficult. The current study aimed to use PCR-RFLP assay to distinguish between F. hepatica and F. gigantica , based on profiles of RFLP, produced by effect of endonucleases on ITS2 of the ribosomal DNA genes from these two species.